Case report: De novo SAMD9L truncation causes neonatal-onset autoinflammatory syndrome which was successfully treated with hematopoietic stem cell transplantation - Caldirola, Maria Soledad (2023)
During recent years, the identification of monogenic mutations that cause sterile inflammation has expanded the spectrum of autoinflammatory diseases, clinical disorders characterized by uncontrolled systemic and organ-specific inflammation that, in some cases, can mirror infectious conditions. Early studies support the concept of innate immune dysregulation with a predominance of myeloid effector cell dysregulation, particularly neutrophils and macrophages, in causing tissue inflammation. However, recent discoveries have shown a complex overlap of features of autoinflammation and/or immunodeficiency contributing to severe disease phenotypes. Here, we describe the first Argentine patient with a newly described frameshift mutation in SAMD9L c.2666delT/p.F889Sfs*2 presenting with a complex phenotypic overlap of CANDLE-like features and severe infection-induced cytopenia and immunodeficiency. The patient underwent a fully matched unrelated HSCT and has since been in inflammatory remission 5 years post-HSCT.